Microbial Electrochemically Assisted Treatment Wetlands: Current Flow Density as a Performance Indicator in Real-Scale Systems in Mediterranean and Northern European Locations - Peñacoba-Antona, Lorena; Ramirez-Vargas, Carlos Andres; Wardman, Colin; Carmona-Martinez, Alessandro A.; Esteve-Núñez, Abraham; Paredes, Diego; Brix, Hans; Arias, Carlos Alberto (Frontiers in Microbiology, 2022)
A METland is an innovative treatment wetland (TW) that relies on the stimulation of electroactive bacteria (EAB) to enhance the degradation of pollutants. The METland is designed in a short-circuit mode (in the absence of an external circuit) using an electroconductive bed capable of accepting electrons from the microbial metabolism of pollutants. Although METlands are proven to be highly efficient in removing organic pollutants, the study of in situ EAB activity in full-scale systems is a challenge due to the absence of a two-electrode configuration. For the first time, four independent full-scale METland systems were tested for the removal of organic pollutants and nutrients, establishing a correlation with the electroactive response generated by the presence of EAB. The removal efficiency of the systems was enhanced by plants and mixed oxic–anoxic conditions, with an average removal of 56 g of chemical oxygen demand (COD) mbed material–3 day–1 and 2 g of total nitrogen (TN) mbed material–3 day–1 for Ørby 2 (partially saturated system). The estimated electron current density (J) provides evidence of the presence of EAB and its relationship with the removal of organic matter. The tested METland systems reached the max. values of 188.14 mA m–2 (planted system; IMDEA 1), 223.84 mA m–2 (non-planted system; IMDEA 2), 125.96 mA m–2 (full saturated system; Ørby 1), and 123.01 mA m–2 (partially saturated system; Ørby 2). These electron flow values were remarkable for systems that were not designed for energy harvesting and unequivocally show how electrons circulate even in the absence of a two-electrode system. The relation between organic load rate (OLR) at the inlet and coulombic efficiency (CE; %) showed a decreasing trend, with values ranging from 8.8 to 53% (OLR from 2.0 to 16.4 g COD m–2 day–1) for IMDEA systems and from 0.8 to 2.5% (OLR from 41.9 to 45.6 g COD m–2 day–1) for Ørby systems. This pattern denotes that the treatment of complex mixtures such as real wastewater with high and variable OLR should not necessarily result in high CE values. METland technology was validated as an innovative and efficient solution for treating wastewater for decentralized locations.